STUDY OF SORPTION OF CU(II) IONS ON VERMICULITE-BASED SORBENT MODIFIED WITH DIETHANOLAMINE - Kholmurodova , S; Muminova , Sh; Kobulova , S; Alikulova , I; Boboyeva , M; Turayeva , S (INTERNATIONAL JOURNAL OF SCIENCE-INNOVATIVE RESEARCH, 2025)
The article covers vermiculite activated in strong acid, its pore formation, modification with hydrolyzed polyacrylonitrile. Also, experiments were carried out on the attachment of the obtained composite sorbent with monomers containing the amine group and the preparation of a highly selective sorbent for Cu(II) ion. The obtained results were tested by SEM and X-ray structural element analysis. Tests on absorption of benzene vapors by adsorption were carried out in the Mac-Ben-Bakr apparatus and appropriate adsorption and desorption isotherms were obtained, its surface area, monolayer capacity and pore sizes were given.